Recent advances in molluscum contagiosum virus research - Bugert, Joachim J.; Darai, Gholamreza (Viral zoonoses and food of animal origin, 1997)
Molluscum contagiosum virus (MCV) and variola virus (VAR) are the only two poxviruses that are specific for man. MCV causes skin tumors in humans and primarily in children and immunocompromised individuals. MCV is unable to replicate in tissue culture cells or animals. Recently, the DNA sequence of the 190 kbp MCV genome was reported by Senkevich et al. MCV was predicted to encode 163 proteins of which 103 were clearly related to those of smallpox virus. In contrast, it was found that MCV lacks 83 genes of VAR, including those involved in the suppression of the host response to infection, nucleotide biosynthesis, and cell proliferation. However, MCV possesses 59 genes predicted to code for novel proteins including MHC-class I, chemokine and glutathione peroxidase homologs not found in other poxviruses. The MCV genomic data allow the investigation of novel host defense mechanisms and provide new possibilities for the development of therapeutics for treatment and prevention of the MCV infection.
Gesehen am 05.09.2024